The Cambridge introduction to twentieth-century American poetry - Beach, Christopher, 1959- (Cambridge introductions to literature., 2003)
The Cambridge Introduction to Twentieth-Century American Poetry is designed to give readers a brief but thorough introduction to the various movements, schools, and groups of American poets in the twentieth century. It will help readers to understand and analyze modern and contemporary poems.